The Effect of Financial Literacy on the Financial Management of Students - Ester Halawa; Maria Magdalena Bate’e; Nanny A. Bu’ulolo; Aferiaman Telaumbanua (Golden Ratio of Data in Summary, 2024)
This study aims to determine the effect of financial literacy on financial management of SMA Negeri 1 Ulunoyo students and the magnitude of the effect of financial literacy on financial management of SMA Negeri 1 Ulunoyo students. The method used in this research is quantitative method. The data collection technique used a questionnaire (Likert Scale). Data analysis techniques used to strengthen questionnaire data are validity test, reliability test, correlation coefficient, linear regression, determinant coefficient, hypothesis testing, normality test, multicollinearity test and heteroscedasticity test. This study used 58 respondents with Simple Random Sampling data collection technique. The results of this study indicate that Financial Literacy affects the Financial Management of SMA Negeri 1 Ulunoyo, South Nias Regency by 54.8%, while 45.2% is influenced by factors not in this study. With increased financial literacy, students will increasingly manage their finances wisely, carefully and regularly by applying indicators of each financial literacy variable and financial management variable, so that students can prepare for future needs and finances.